Marketing of commercial broiler (dressed chicken) in selected towns in the first district of Iloilo, 1997. - Leysa, Thea C.
This research study tried to describe, analyze, and compare the existing market opration system of the selected towns in the first district of Iloilo. It also determines the marketing cost incurred, the marketing and net margins received and the problems encountered by both the producer and traders., In this study it was found out that the producer also acted as the wholesaler. The producer-wholesaler distributed or delivered the dressed chicken in retail outlets like the public markets and restaurants. The traders could act as retailers or wholesaler-retailers. There were fifty-three (53) respondents gathered from different towns. These respondents were the retailers (27), the contract growers, twenty-five (25) and the producer. Each respondent has at least realized profit from this venture. The researchers found out that retailers obtained the lowest net profit because the marketing costs were disregarded in pricing the product. The contract growers incurred a total production cost of P6.20 per head of chicken for the labor and depreciation of invested capital (i.e building and equipment). The integrator, on the other hand, spent a total of P25.08 per head for the variable production costs incurred (i.e. chicks, feeds, medicines and veterinary assistance). Both of them gained a net profit of P 8.80 per head of live chicken for the contract grower and P 12.72 per head of dressed chicken for the integrator. In the marketing aspect, the middlemen involved were only retailers. The average marketing cost of the retailers was P 1.79 per kilogram while that of the integrator-producer was P 10.20 er head. The retailers realized an average net profit of P 3.56 per kilogram. The researchers had a difficulty in assessing the net profit of the integrator-producer as a producer and as a wholesaler because of its overlapping functions. Contract growers had sometimes faced a problem of alter harvest, which resulted to less weight of chicken or added cost on feeds. On the other hand, retailers complained about the difficulty in coping up with chicken's price fluctuations and occasional power failure.